1983
DOI: 10.1103/physrevlett.51.51
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy and Quantization in Condensed Matter Physics

Abstract: It is shown that the integers found by Thouless

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
531
0
6

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 597 publications
(541 citation statements)
references
References 6 publications
4
531
0
6
Order By: Relevance
“…[2][3][4][5][6] For example, the relation between the quantized number C and the non-degenerate many-body ground state wave functions |Ψ(φ, ϕ) obeying twisted boundary conditions parametrized by the pair of angles 0 ≤ φ, ϕ ≤ 2π for a gas of electrons confined in twodimensional (position) space and subjected to a uniform magnetic field is C = − i 2π …”
Section: Introduction and Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] For example, the relation between the quantized number C and the non-degenerate many-body ground state wave functions |Ψ(φ, ϕ) obeying twisted boundary conditions parametrized by the pair of angles 0 ≤ φ, ϕ ≤ 2π for a gas of electrons confined in twodimensional (position) space and subjected to a uniform magnetic field is C = − i 2π …”
Section: Introduction and Resultsmentioning
confidence: 99%
“…24 We will call this the "sum rule". The current distribution among subbands, which is also quantized in each subband, was obtained by Thouless et al 11 In their famous paper, they found that the subband Hall conductivities are the integer-valued solutions of the Diophantine equation.…”
Section: B Distribution Of Hall Conductivities and Splitting Of Enermentioning
confidence: 99%
“…Here, the symbol CS (3) (3) to the noncommutative algebra obeyed by the components of the projected position operator through the noninteracting groundstate expectation value of their 3-bracket. Because the position operator and its projection are unbounded operators and because Wannier states may not be exponentially localized if the Bloch states have a topological character, 60,61 a regularization procedure is needed to compute Eq.…”
Section: Noncommutative Geometrymentioning
confidence: 99%
“…The index in this case is the sum of the (first) Chern numbers obtained for each of the fully filled Landau bands, and the associated physical observable is the Hall conductance. [2][3][4] The fractional quantum Hall effect (FQHE) 5 results from the effects of electron-electron interactions when the Landau levels are partially filled with electrons, for certain rational filling fractions. 6 More examples of topological states of matter that are comprised of noninteracting fermions have been discovered recently, [7][8][9][10][11][12][13][14][15][16] and have been classified according to discrete symmetries they respect or not, and the dimensionality of space in which the particles propagate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation